Advanced glycation end products, galectin-3, matrix metalloproteinase-9 activity in men with heart failure and concomitant benign prostatic hyperplasia with androgen deficiency - V.S. Nedzvetsky; O.Yu. Sirenko; V.A. Tkachenko; O.V. Kuryata (Medičnì Perspektivi)
The aim was to evaluate serum levels of matrix metalloproteinases-9 activity, advanced glycation end products, galectin-3, C-reactive protein in men with heart failure and benign prostatic hyperplasiawith testosterone deficiency. The testosterone level was determined by immune-enzyme analysis. The content of advanced glycation end products in plasma were analysed by quantitative autofluorescence. The metalloproteinases-9 activity was estimated with fluorometry. The level of galectin-3, C-reactive protein was determined by immune-enzyme analysis. 1st group was made up by the men with heart failure and benign prostatic hyperplasia with testosterone deficiency; 2nd group – by the men without testosterone deficiency. The men with heart failure and benign prostatic hyperplasia with testosterone deficiency had a significantly higher level of advanced glycation end products, galectin-3, matrix metalloproteinases-9 activity in comparison with men with heart failure without testosterone deficiency (p<0.001). Correlation relations between serum advanced glycation end products in patients of the main group with age, ejection fraction, testosterone level were determined – r=0.48 (p<0.001), r=-0.62 (p<0.001), r= -0.66 (p<0.001) respectively. Receiver operating characteristic analysis for predictive role in heart failure with preserved ejection fraction have shown high degree of sensitivity and specificity for advanced glycation end products in serum (p<0.001). Middle-aged men with heart failure with preserved ejection fraction and benign prostatic hyperplasia with testosterone deficiency are characterised by increased serum advanced glycation end products, galectin-3, matrix metalloproteinases-9 activity, C-reactive protein. Serum advanced glycation end products are potential biomarkers of development of heart failure with phenotype of preserved ejection fraction in this cohort.